Controle de produção de gado leiteiro - Silva, Matheus Pacheco da (2018)
In a very simplified way, the profitability of dairy catlle production is in the positive result of the relation between the cost of feeding and the quantity and quality of milk produced. In addition to the cost of food, are the costs of purchasing the herd, treatment of diseases, insemination, among others. However, the relationship between the cost of feeding and the milk produced by each animal determines the viability of maintaining each milky cow. The control of the production by animal can be difficult when the milk produced is not individualized per animal. However, the average of this production can help determine the viability of the lot and define the profitability of the producer. Aiming to help costs and expenses of dairy cattle production, as a result of this work, a web system was developed to assist in the management of milk catlle. The system allows the storage data of expenses and dairy milk production.